The Vernakularisation in The Native Interpretation Product: Analysis of Speech Level in Bisri Mustofa’s Tafsir Al-Ibriz - Shofa, Ida Kurnia (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2024)
This study aims to explain the speech level of the Javanese language in Bisri Mustofa's Tafsir al-Ibriz. Bisri Musthofa's Tafsir al-Ibriz has a great locality value, used Javanese as an interpretation of the Qur’an text. As it is known that Java has language etiquette or politeness rules that are used to distinguish between disrespectful language (rough/ngoko) and respectful language (smooth/madya-krama) which indicates strata or social status. Through library research and using a sociolinguistic approach, this study shows that Tafsir al-Ibriz contains a language hierarchy (speech level) in the dialogues contained in the Qur'an which is interpreted using Javanese language rules according to their social position. However, in its application, Bisri found inconsistencies in the use of the language level used, such as dawuh and ngendika sentences. In the dialogue of the Qur'an, the utterances conveyed by Allah to His servants, the speech of a leader to the people, the speech of parents to their children, are expressed using the ngoko language. Vice versa, the speech conveyed by servants to Allah, children to their parents, subordinates to their leaders is expressed using the language of manners, and dialogues with others, such as Prophet Musa and Prophet Harun are interpreted using ngoko language. Thus, it can be understood that Tafsir al-Ibriz uses the ngoko-madya-krama language level as a manifestation of the Javanese symbolic classification system based on several categories of high-low, formal-informal, or foreign-ordinary